The Influence of Teacher's Personality on Students' Learning Interest in the Field of Islamic Religious Education Studies - Muzakki, Zubairi; Amini, Izzat (Universitas Al-Amien Prenduan, 2023)
This study aims to determine the effect of the teacher's personality on students' learning interest in the field of Islamic religious education at SMK Angkasa 2, Tangerang Regency. The research method used in this study is a quantitative research method with a causative type. The population taken in this study was a sampling population of all 563 students of Angkasa Pura 2 Vocational School, Tangerang Regency, so that a sample of 30 students was taken. The data was obtained through the use of a questionnaire instrument that measures the dimensions of the teacher's personality and student learning interest. Regression analysis was used to analyze the data and identify the relationship between teacher personality and student interest in learning. The results of the study show that the teacher's personality has a significant influence on students' learning interest in the field of study of Islamic Religious Education. This is indicated by the magnitude of the influence that is equal to 47.94%. The implication of this research is the important role of the teacher's personality in creating a positive learning environment and stimulating students' interest in learning. Therefore, it is hoped that teachers can develop and improve aspects of their personality related to warmth, emotional intelligence and openness, so that they can motivate students to have a high interest in learning Islamic religious education.